Numerical Studies of Astrophysical Objectsat Fesenkov Astrophysical Institute (FAI) - Assylkhan Bibossinov; Denis Yurin; Chingis Omarov
Numerical studies of astrophysical objects are a relatively new direction in Fesenkov Astrophysical Institute (FAI) and is mainly represented by the Laboratory of Cosmology, Stellar Dynamics and Computational Astrophysics. The lab seeks to understand the evolution of gravitating systems at various scales – from star clusters to galaxies to large-scale structure of the universe as a whole, and tackles these problems both through analytical methods and through numerical simulations. The particular focus is on numerical simulations of star clusters, especially those found in active galactic nuclei – this is a topic of oldestablished collaboration with colleagues from Astronomisches Rechen-Institut (Heidelberg) and National Astronomical Observatories of China (Beijing). The prominent example is STARDISK project dedicated to the numerical research of active galactic nuclei as multicomponent systems composed of compact stellar cluster, gaseous accretion disk and a supermassive black hole. It is demonstrated that an accretion disk can noticeably decelerate stars and thus enhance the accretion rate onto the black hole. In 2013 FAI hosted the MODEST-13 International Workshop dedicated to modeling of star clusters. Recently a new project has been approved aimed at construction of triaxial equilibrium N-body systems that can be of great help in various numerical experiments with disk galaxies. There are also long standing plans to perform cosmological simulations of large scale structures to test a new approach to dark matter and energy actively developed at FAI. For numerical calculations, FAI has a small, but growing computer cluster consisting of several high-performance computing servers equipped with computational GPU cards.
Keywords: Astrophysics